Implementasi Aplikasi E-Commerce untuk Flamboyant Bakery dengan Menggunakan Python Flask - Safari Herawan, Mochamad Hardy; Ma’sum, Hadiansyah (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2024)
The objective of this research is to assist Flamboyant Bakery in creating a sales application. The primary goal is to develop an E-Commerce application that can overcome operational constraints, such as marketing limitations in a wider market, difficulties in acquirinjg new customers, and a lack of media that can enhance the company's credibility. The sales application aims to expand the market, improve information accessibility, and introduce the company's profile. It also facilitates the recording of purchase and search history by customers. Therefore, it is expected to enhance Flamboyant Bakery's operational efficiency and competitiveness in a highly competitive market. Additionally, this research examines marketing methods and strategies that can be utilized in the app's development. The app design is based on a thorough analysis of customer needs and market trends, with the goal of providing an optimal solution for Flamboyant Bakery. This approach aims to create a sales application that meets the company's operational needs while also effectively attracting new customers and retaining existing ones. This website design was created using the Python programming language with the Flask framework and for data storage/database using SQLite.